Reactivity, Selectivity, and Reaction Mechanisms of Aminoguanidine, Hydralazine, Pyridoxamine, and Carnosine as Sequestering Agents of Reactive Carbonyl Species: A Comparative Study. (17th February 2016) - Colzani, Mara; De Maddis, Danilo; Casali, Gaia; Carini, Marina; Vistoli, Giulio; Aldini, Giancarlo
Abstract: Reactive carbonyl species (RCS) are endogenous or exogenous byproducts involved in the pathogenic mechanisms of different oxidative‐based disorders. Detoxification of RCS by carbonyl quenchers is a promising therapeutic strategy. Among the most studied quenchers are aminoguanidine, hydralazine, pyridoxamine, and carnosine; their quenching activity towards four RCS (4‐hydroxy‐ trans ‐2‐nonenal, methylglyoxal, glyoxal, and malondialdehyde) was herein analyzed and compared. Their ability to prevent protein carbonylation was evaluated in vitro by using an innovative method based on high‐resolution mass spectrometry (HRMS). The reactivity of the compounds was RCS dependent: carnosine efficiently quenched 4‐hydroxy‐ trans ‐2‐nonenal, pyridoxamine was particularly active towards malondialdehyde, aminoguanidine was active towards methylglyoxal and glyoxal, and hydralazine efficiently quenched all RCS. Reaction products were generated in vitro and were characterized by HRMS. Molecular modeling studies revealed that the reactivity was controlled by specific stereoelectronic parameters that could be used for the rational design of improved carbonyl quenchers. Abstract : Carbonyl quenchers : A protein carbonylation assay is used to quantify the extent of modification of a model protein upon its in vitro incubation with fixed concentrations of different reactive carbonyl species (RCS) and increasing concentrations of sequestering agents. The assay shows preferential reactivity of some sequestering agents versus given RCS. The reaction products obtained from the RCS and the sequestering agents are identified by HRMS.